AI Integration with ServiceNow and CMDB: Revolutionizing Industries and Society - Chinthapatla, Yuvaraja (Journal of Science & Technology, 2024)
The integration of Artificial Intelligence (AI) with Configuration Management Database (CMDB) and ServiceNow, a leading IT service management platform, represents a pivotal advancement in organizational efficiency, data-driven decision-making, and transformative innovation. This comprehensive exploration delves into the profound significance of AI integration with CMDB and ServiceNow, elucidating its multifaceted applications across diverse industries and addressing its far-reaching implications for the future. Through a detailed analysis spanning 20,000 words, this article endeavors to provide an exhaustive understanding of this transformative synergy and its potential to reshape the technological landscape, drive organizational excellence, and foster societal progress.